Implementasi Teori Fenomenografi Marton Pada Mata Kuliah Ekonomi Internasional (Studi di Program Studi Pendidikan Ekonomi FKIP Universitas Samawa) - Fadillah, Nurul; Suharli, Suharli; Andriani, Nining (Fakultas Keguruan dan Ilmu Pendidikan Universitas Samawa, 2022)
This study aims to analyze the predominant learning approach used by students based on phenomenography theory. This research is focused on a learning approach based on phenomenography theory (1) Deep Approach learning approach. (2) Surface Approach learning approach. This type of research used in this research is descriptive qualitative research, using a phenomenographic approach. Obtaining data was done by using the thinking aloud test method, and semi-structured interviews. Data analysis was performed on 6th-semester students through several stages (1) Preparation of transcripts (2) Data reduction (3) Data organization (4) Category of Description. Furthermore, to test the validity of the data, a triangulation of methods was carried out to check the correctness of the data obtained from the informants using different data collection techniques. Based on the data analysis, it can be concluded that the sixth semester of economic education students at the Faculty of Teacher Training and Education at Samawa University dominantly use the Surface Approach, while a small proportion uses the deep learning approach.